Perceived Discrimination and Motivation to Pursue Higher Education in Ethiopian-Origin Students: The Moderating Role of Ethnic Identity - Slobodin, Ortal; Icekson, Tamar; Herman, Lee; Vaknin, Ofri (Frontiers in Psychology, 2021)
Research has increasingly recognized the adverse effects of perceived discrimination on the academic outcomes of children and adolescents from ethnic and racial minority backgrounds. However, little is known about the association between perceived discrimination and the motivation of ethnic minority students to pursue higher education. Guided by an academic resilience framework, the current study examined the relationship between perceived discrimination and two types of motivation to pursue higher education (personal/career-driven and expectation-driven) among Ethiopian undergraduate students in Israel. In addition, we examined the role of ethnic identity as a potential moderator of this relationship. Participants were 183 undergraduate students of Ethiopian origin (77 % females) who studied in 18 different higher-education institutes. Participants completed self-report questionnaires concerning their experiences of perceived discrimination, affiliation with their Ethiopian identity, and their reasons for pursuing higher education. Results showed that frequent discrimination experiences were positively related to a stronger ethnic identity and to higher levels of personal/career motivation to pursue higher education. Ethnic identity moderated the relationship between perceived discrimination and personal/career motivation so that the association was significant under low and moderate levels of ethnic identity but not under high levels. Our findings suggest that the awareness of discrimination may motivate students to pursue higher education and succeed in academia. However, the motivating force of perceived discrimination diminishes under high levels of ethnic identification. Further investigation is needed to explore how discrimination and ethnic identity work together to impact academic motivation in different developmental stages and socio-cultural contexts.